Implementation Of The Sale And Purchase Agreement And The Status Of Ownership Of Land Rights At Apartment In Payon Amartha View Of Semarang - Riska Fauziana; Rizal Anugrah Bachriar; Anis Mashdurohatun (Jurnal Akta, 2019)
The study entitled "Implementation of the Sale and Purchase Agreement and the Status of Ownership of Land Rights at Apartment in Payon Amartha View of Semarang" aims to: 1) Understand the process of buying and selling apartments. 2) To know about the status of ownership of land rights of the apartment.Theresearch method in this journal uses a sociological Juridical approach with the specification of the data collection method to Obtain the data that will be used as the thesis of material through an interview with the manager and the marketing of apartment in Payon Amartha View of Semarang, or by observation in the form of roomates surveillance systematically Involved in Obtaining data. Afterwards will be conducted analysis of the data Obtained from various sources.The results of the research indicate that: 1) The process of buying and selling apartments begins with payment of the Booking Fee Followed by the signing of the Temporary Deed of Sale and Purchase (TDSP) as a legitimate and strong evidence that it has made a sale and purchase. 2) The ownership status of the buyer of the apartment is the Strata Title Certificate.Keywords: Sale And Purchase; Ownership Rights To The Apartment.